Pola Asuh Anak: Tinjauan Kitab Amsal 29:17 - Dewi Zakarias; Valensia Ngongo; Yeheskiel Obehetan (Sekolah Tinggi Teologi Shema Cianjur, 2025)
This study aims to examine parenting based on the principles of Proverbs 29:17 and its impact on the formation of children's character and personality. This study is motivated by the importance of the role of parents in educating children effectively according to biblical teachings, in order to create a harmonious family environment and support the development of children as a whole. This research uses a library research method with a qualitative approach, in which data is collected from various written sources such as books, journals, and relevant documents, then analyzed in depth. The results show that parenting based on biblical values can positively shape children's moral, spiritual and social character. This research is expected to contribute to parents in implementing faith-based parenting and biblical values, so as to help produce a generation that is independent, ethical, and has good character according to the teachings of the Christian faith.